Antiarrhythmic drug therapy after catheter ablation for atrial fibrillation has no impact on recurrences, cardiovascular events and mortality – insights from the German Ablation Registry. (14th October 2021) - Schleberger, R; Metzner, A; Kuck, K H; Andresen, D; Willems, S; Hoffmann, E; Deneke, T; Eckardt, L; Brachmann, J; Hochadel, M; Senges, J; Rillig, A
Abstract: Background: Data on the optimal treatment strategy for antiarrhythmic drug therapy (AAD) after atrial fibrillation (AF) catheter ablation are inconsistent. While AAD potentially stabilizes sinus rhythm, it also increases the patients' treatment burden. Methods: Patients from the prospective German Ablation Registry (n=3275) discharged with or without AAD after AF catheter ablation were compared regarding long-term success, cardiovascular events and patient reported outcome. Results: In patients with paroxysmal AF (n=2138) recurrence and rehospitalization rates did not differ when discharged with (n=1051) or without (n=1087) AAD (recurrence: adjusted odds ratio (OR) 1.13, 95% confidence interval (CI) [0.95–1.35]; rehospitalization: OR 1.08, 95% CI [0.90–1.30]). The reablation rate was higher and reduced treatment satisfaction was reported more often in those discharged with AAD (reablation: OR 1.30, 95% CI [1.05–1.61]; reduced treatment satisfaction: OR 1.76, 95% CI [1.20–2.58]). Similar rates of recurrences, rehospitalisations, reablations and treatment satisfaction were found in patients with persistent AF (n=1137) discharged with (n=641) or without (n=496) AAD (recurrence: OR 1.22, 95% CI [0.95–1.56]; rehospitalization: OR 1.16, 95% CI [0.90–1.50]; reablation: OR 1.21, 95% CI [0.91–1.61]; treatment satisfaction: OR 1.24, 95% CI [0.74–2.08]). The incidence of cardiovascular events and mortality did not differ at follow-up in paroxysmal and persistent AF patients discharged with or without AAD. Conclusion: The rates of recurrences, cardiovascular events and mortality did not differ between patients discharged with or without AAD after AF catheter ablation. However, AAD should be considered carefully in patients with paroxysmal AF, in whom it was associated with a higher reablation rate and reduced treatment satisfaction. Funding Acknowledgement: Type of funding sources: None.